A phase 1 study to evaluate the feasibility and efficacy of the addition of ropeginterferon alpha‐2b to imatinib treatment in patients with chronic phase chronic myeloid leukemia (CML) not achieving a deep molecular response (molecular remission 4.5)—AGMT_CML 1. Issue 5 (19th August 2020) - Heibl, Sonja; Buxhofer‐Ausch, Veronika; Schmidt, Stefan; Webersinke, Gerald; Lion, Thomas; Piringer, Gudrun; Kuehr, Thomas; Wolf, Dominik; Melchardt, Thomas; Greil, Richard; Thaler, Josef
Abstract: The goal of current management of patients with chronic phase chronic myeloid leukemia (CML) is to reach treatment‐free remission with sustained deep molecular remission (DMR) being the prerequisite therefor. Second‐generation tyrosine kinase inhibitors can induce deeper and faster remission than imatinib, but are often associated with severe adverse events (AEs). The combination of pegylated interferon (IFN) with imatinib was shown to induce higher molecular remissions than imatinib alone in two studies. Treatment discontinuation rates due to IFN induced AEs were high in both studies. To investigate safety, tolerability (primary objective), and efficacy (secondary objective) of the combination of imatinib with ropeginterferon alpha‐2b this phase I study was initiated. Twelve patients were planned to be enrolled. Nine patients completed the study according to protocol. Three patients terminated the study early, one due to occurrence of a dose‐limiting toxicity (neutropenia grade 3), one due to an AE (panic attacks grade 2) and one due to the patient's decision. Tolerability was good, non‐hematologic AEs were mainly grade 1/2, hematologic AEs were mainly neutropenias. No new AEs were reported for the combination of imatinib and ropeginterferon alpha‐2b. In a nondose‐dependent manner the addition of ropeginterferon alpha‐2b led to the achievement of a DMR in four out of nine patients after a treatment duration of 18 months. The combination of imatinib and ropeginterferon alpha‐2b is safe and showed in this phase I study the ability to deepen the molecular response in patients with chronic phase CML not achieving a DMR with imatinib alone.